Pengaruh Model Pembelajaran Example Non Example Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Tematik V Kelas V UPT SDN 204 Gresik - Siti Maimunah; Anarisa (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2023)
This study aims to describe the effect of the example non-example learning model on student learning outcomes in thematic subjects V grade V UPT SD Negeri 204 Gresik. Based on the results obtained by researchers from initial observations of fifth grade students at UPT SD Negeri 204 Gresik, Kedamean District, Gresik Regency, in thematic subjects (Theme 5 Ecosystem, Sub-theme 1 Ecosystem Component), it can be concluded that 100% of the 14 students with learning outcomes in the category of achieving KKM with an average of 93.6. This type of research is quantitative experimental method with a one-shot cast study design. This research uses nonprobability sampling technique with saturated sampling method. The sample in this study were fifth grade students at UPT SD Negeri 204 Gresik. Student learning outcomes using the example non-example learning model in fifth thematic subjects for class V UPT SD Negeri 204 Gresik are in the classical complete category, because 100% of students are in the complete category. Based on the model summary table, it is known that R is worth 0.885, which means the correlation between the independent variable (Example Non Example Learning Model) and the dependent variable (learning outcomes) is in the Very high category. Meanwhile, according to the value of R Square is 0.783, it can be interpreted that the example non example learning model affects student learning outcomes by 78.3% while the remaining 21.7% is influenced by other variables not discussed in this study.